PENGARUH PARTISIPASI DAN KEPUASAN ANGGOTA TERHADAP KINERJA KOPERASI PRODUSEN CITRA KINA RAYA - Safitri, Rina; Prasetyo, Agus Subhan; Mariyono, Joko (Jurnal Agribisnis Wijaya Putra Surabaya, 2022)
A cooperative is a business entity that uses the principles of kinship and cooperation in its business. The success and progress of Koperasi Produsen Citra Kina Raya, a cooperative name, were not achieved without members’ participation and satisfaction as holders and users (dual identity). The study aimed (1) to analyze the members’ participation, satisfaction, and cooperatives’ performance; (2) to analyze the effect of members’ participation and satisfaction on cooperatives’ performance in Koperasi Produsen Citra Kina Raya. The study was implemented from January to February 2022. This study employed a survey method using a quantitative approach. The sample size was 78 respondents. Data were collected by scoring answers to the instruments research, which are then analyzed statistically to determine the level of participation, satisfaction, and performance and the influence between the variables. The results show that : (1) The level of participation, satisfaction, and performance was classified well with a percentage score of 79,5%, 83,3%, and 86,5%; (2) There is a positive effect and significance between the independent and dependent variables. The study concludes that participation is well caused by the economic and social benefit that members receive, while the members’ satisfaction affects participation and transaction in the cooperative. Suggestions by the authors are that the cooperative should maintain and increase members’ satisfaction through increasing quality service, trust in management, increasing participation in decision making, and hiring the agriculture machine.